Alteraciones de la afectividad y aborto en adolescentes y adultas jóvenes. - Andaluz Bustillos, Ariana Monserrath (2024)
Abortion is the termination of pregnancy before the twentieth week, or the expulsion of the fetus, which can be spontaneous or provoked. It is considered a traumatic and violent experience that threatens the integrity of women. Hence, it is so relevant to study the effects of women who experience pregnancy loss, because for many women it can be a traumatic process that can lead to suffering various psychological alterations. The objective of the study focused on analyzing the alterations of affectivity in patients who have experienced an abortion. The research corresponds to a bibliographic review of cross-sectional design and descriptive level. The population was comprised of 220 scientific articles published from 2014 to 2024 in Spanish and English languages. The sample involves a non-probabilistic category for convenience and is composed of 60 documents that correspond to quantitative studies. The selection criteria were applied along with the bibliographic search algorithm for the screening process. The sources of information involve the use of the following databases: PubMed, Semantic Scholar, ScienceDirect, PubMed Central, Dialnet, Springer Link, Multidisciplinary Digital Publishing Institute, Google Scholar, among others. Literature review and documentary quality review were used as techniques; In the case of instruments, the bibliographic review sheet and the CRF-QS matrix. Regarding the results, it was determined that the emotional alterations with the most prevalence in women who have suffered an abortion are: Anxiety, post-traumatic stress disorder (PTSD) and depression indicated in different studies as the pathologies with the highest percentage of risk; There are various conditions that manifest themselves in a lower percentage such as: phobias, bipolarity and obsessive-compulsive disorder. As stated previously, this is because abortion can imply a key point of imbalance in a woman's life, leading to an emotional alteration that, if not taken into account, would develop into a pathology at the level of her mental health, For this reason, it is a currently controversial topic that is taken from two different points of view, in society there is a very superficial belief in abortion where the whole topic is not delved into, leaving aside the feelings and physical and psychological consequences to which that women face.